Phenotypic stability of advanced hybrids for yield in early and main potato (Solanum tuberosum) crop - SINGH, S V; GAUR, P C; PANDEY, S K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted at modipuram during 1994-96 to assess 24 genotypes for yield at 60, 70, 80 and 90 days ofharvest of potato (Solanum tuberosum L.). The pooled analysis showed significant variance due to genotype x environmentinteraction. The predictable component of G X E variance was not significant but the variance due to deviationfrom regression was significant. The data for early harvest (60 and 70 days: Group I) and medium duration harvest (80and 90 days: Group II) were also analysed separately for identifying stable early bulking and medium bulking genotypes.In Group I 'JX 235' gave higher yield than the best control variety 'Kufri Jawahar' and low value of deviationfrom regression (S2 di 0.54) indicating good stability and predictability of performance. In Group II, 'JX 235' (45.55tannes/ha) and 'JX 118' (43.99 tannes/ha) gave significantly higher yield than the varieties 'Kufri Badshah' (39.91tonnes/ha) and 'Kufri Jawahar' (40.11 tonnes/ha). Both genotypes showed non-significant deviation from regressionindicating their stability of performance over environments